Photodynamic therapy of diseases of the head and neck - Biel, Merrill A. (Plural Pub., 2008)
Presents the background, methodology and outcomes for Photodynamic Therapy (PDT) treatment of diseases of the head and neck. The author, an expert and pioneer in this field, discusses the indications for PDT treatment with their advantages and pitfalls. As PDT is an approved therapy for treatment of head and neck cancers in many countries in the world, this text provides the clinician and basic researcher with an understanding of PDT and how to successfully employ it for the successful treatment of head and neck cancers. This comprehensive book is unique in that no other scientific text has devoted itself to the presentation of PDT treatment of head and neck and upper aerodigestive tract disease, a treatment area that has its own unique treatment issues. This is the first text for clinicians and researchers who need to perform or learn about PDT of the head and neck. The text includes both established treatment modalities as well as new and upcoming treatments, such as the use of PDT to treat antibiotic resistant infections.